Comparison of Dental Caries and Oral Hygiene among Children of Working and Non-Working Mothers - Zunaira Iqbal, Seema Shafeeq, Arooj Ul Hassan,, Tahira Ashraf,,Obaid Bajwa, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Mother’s role in improving children’s oral hygiene and reducing the risk of tooth decay is undeniable. However, a mother’s employment status has been an important yet ignored aspect to study for its potential impact on the oral hygiene of children. Aim To compare the frequency of dental caries and poor oral hygiene in children of working and non-working mothers Methods: This cross-sectional study was conducted on 260 children divided in two groups (working and non-working mothers). The data was collected using nonprobability convenience sampling. The mothers were briefed about research and data was collected from them. The data was entered and analyzed using SPSS 21. Descriptives were given in form of mean, median, standard deviations, and interquartile ranges. Chi-square test, independent sample t-test, and Mann Whitney U test were applied for the statistical difference of oral hygiene-related variables in the two groups. Results: The mean age of working mothers was 30.97 ± 4.204 years and of non-working mothers was 28.59 ±4.86 years. A significant association of the working status of the mother was found in the lesser frequency of brushing, more consumption of sweets as well as bottle feeding. (p-values<0.05). higher knowledge of negative effects of bottle feeding was reported among working mothers (16.2%) compared to nonworking mothers (8.5%), (p-value<0.001), the assistance in brushing was significantly higher in nonworking mothers (37.7%) compared to working mothers (22.3%), (p-value=0.007). Conclusion:: This study concludes that working mothers have a significantly higher risk of tooth decay, missing tooth, and tooth filling among their children.